2017
DOI: 10.1016/j.jmii.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum pentraxin-3 and tumor necrosis factor-like weak inducer of apoptosis (TWEAK) predict severity of infections in acute decompensated cirrhotic patients

Abstract: High serum PTX/sTWEAK levels and PEW are common in cirrhotic patients with acute decompensation. As compared with low serum PTX and sTWEAK cases, cirrhotic patients with high serum PTX/sTWEAK levels a have higher probability of new severe infections, severe sepsis, septic shock, type 1 hepatorenal syndrome, in-hospital, and 3-month follow-up mortalities. Therefore, high serum PTX/sTWEAK levels on hospital admission predict disease severity and case fatality in cirrhotic patients with acute decompensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Narciso-Schiavon et al [50] analyzed the circulating PTX3 levels in cirrhotic patients and found that higher PTX-3 levels indicated a significantly lower 90-day survival rate (54% vs. 77%). Fan et al [51] also found that acute decompensated patients with high PTX-3 levels had a higher probability of in-hospital mortality (HR: 3.94) and 3-month mortality (HR: 3.52).…”
Section: Prognostic Biomarkers Of Survival Ratementioning
confidence: 94%
“…Narciso-Schiavon et al [50] analyzed the circulating PTX3 levels in cirrhotic patients and found that higher PTX-3 levels indicated a significantly lower 90-day survival rate (54% vs. 77%). Fan et al [51] also found that acute decompensated patients with high PTX-3 levels had a higher probability of in-hospital mortality (HR: 3.94) and 3-month mortality (HR: 3.52).…”
Section: Prognostic Biomarkers Of Survival Ratementioning
confidence: 94%
“…The prevailing opinion nowadays is that systemic PTX3 is induced in patients with chronic liver diseases [11,19] and has a positive predictive value for adverse clinical outcomes [20,21]. Liver cirrhosis is a risk factor for HCC, and PTX3 may also have a role herein [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is only a single study in the literature evaluating serum sTWEAK levels in patients with cirrhosis. In that study, Fan et al 16 have reported that serum sTWEAK levels were significantly higher in acute decompensated cirrhotic patients than controls and serum sTWEAK concentrations were found to be positively correlated with new infections, long hospital stays, high International Journal of Hematology and Oncology medical costs, and high mortality. Our results are not consistent with the findings of that study.…”
Section: Discussionmentioning
confidence: 92%